Identification and Control of Idiosyncratic Risks for Financial Products of the Cultural and Creative Industry - Suqiu, Zhang (2021)
This research explores the discrete and diversified characteristics of the cultural and creative industry (CCI) to identify and control their idiosyncratic risk in the open financial market. This article selects a panel data of cultural and creative companies listed in the Tianjin Cultural Art Exchange Market for the 2011 to 2017 period, to identify the influencing factors of their idiosyncratic risks through a multiple quality signal model. The results show that liquidity, market risk, and the characteristics of the cultural and creative industry have a significant impact on its idiosyncratic risk. It is worth noting that the impact of market risk on the idiosyncratic risk of publicly traded cultural and creative companies is limited within the industry, while trading of the external financial system has no significant impact on the idiosyncratic risk of the cultural and creative industry, therefore incurring no investment substitution effect. This paper concludes that the idiosyncratic risk of the CCI can be identified and controlled based on the liquidity, market risk and trading patterns of the cultural and creative companies listed in an open financial market. This helps creative industry entrepreneurs to assess the risk of their potential investments and policy makers to improve the surveillance mechanisms of the financial system.